Kajian Tafsir Nusantara - Hamzah, Idil; Marwati, Andi (The International Journal of Pegon : Islam Nusantara civilization, 2023)
This article discusses the methodology of writing the al-Munir exegesis by Jalaluddin Thaib. The article employs a literature review method, drawing its sources from various literary works (library research). The findings of this research conclude that the al-Munir exegesis is a significant milestone in the history of exegesis in Indonesia. The work of Buya Jalaluddin Thaib represents an intellectual and spiritual treasure for Muslims, especially in Indonesia. Despite its great potential, a deep understanding of both the author and his work is still not widely disseminated. Buya Jalaluddin Thaib, a scholar from Minangkabau, displayed leadership qualities from a young age. His interest in education continued, including writing books for religious schools and establishing the Association of Religious School Teachers (PGSA) in the Minangkabau region. The al-Munir exegesis, authored by Buya Jalaluddin Thaib, aims to help the community understand the meanings and content of the Quran. It was written to facilitate beginners studying the Quran and to assist Muslims in their worship. The unique characteristics of the Al-Munir exegesis, authored by an Indonesian scholar, particularly from the Minangkabau region, offer hope that this valuable manuscript can be effectively managed to enhance access and preserve intellectual richness in Indonesia. Artikel ini mengulas tentang metodologi penulisan tafsir Al-Munir karya Jalaluddin Thaib. Artikel ini menggunakan metode kepustakaan yang dimana sumber datannya bersumber dari literatur-literatur (library research). Hasil dari penelitian ini menyimpulkan bahwa tafsir Al-Munir merupakan salah satu babak penting dalam sejarah pemikiran tafsir di Indonesia. Karya Buya Jalaluddin Thaib ini merupakan harta intelektual dan spiritual bagi umat Muslim, terutama di Indonesia. Meskipun memiliki potensi yang besar, pemahaman mendalam tentangnya masih belum tersebar luas, baik mengenai pengarangnya maupun karyanya. Buya Jalaluddin Thaib adalah seorang ulama asal Minangkabau yang menunjukkan bakat kepemimpinan sejak usia dini. Minatnya dalam dunia pendidikan terus berlanjut, termasuk dalam penulisan buku untuk pendidikan di sekolah agama, serta pendirian Persatuan Guru-Guru Sekolah Agama (PGSA) se-Minangkabau.Tafsir Al-Munir yang ditulis oleh Buya Jalaluddin Thaib memiliki tujuan untuk membantu masyarakat memahami makna dan kandungan isi Al-Qur'an. Penulisannya bertujuan untuk memfasilitasi pemula yang mempelajari Al-Qur'an serta memudahkan umat Muslim dalam pelaksanaan ibadah. Karakteristik unik dari Tafsir Al-Munir yang ditulis oleh ulama asli Indonesia, khususnya Minangkabau, memberikan harapan bahwa manuskrip berharga ini dapat dikelola dengan baik untuk mempermudah akses dan melestarikan kekayaan intelektual di Indonesia.